An interview with Paul A. Samuelson - William A. Barnett; Paul A. Samuelson (Turkish Economic Association, 2009)
Microeconomics, Macroeconomics, Trade, Welfare Economics,Finance Theory, Capital Theory, Revealed Preference, Overlapping,Generations
Keywords: 330